Additive effects of rapamycin and aspirin on dendritic cell allostimulatory capacity. (3rd September 2015) - Roehrich, Marc-Estienne; Wyss, Jean-Cristophe; Kumar, Rajesh; Pascual, Manuel; Golshayan, Dela; Vassalli, Giuseppe
Abstract: Acting as antigen presenting cells, mature dendritic cells (DCs) initiate both innate and adaptive alloimmune responses. However, immature DCs are weak immunostimulators and mediate tolerogenic effects under certain conditions. Tolerogenic activities of immature DCs can be enhanced by pharmacological agents. Here, we compared pharmacological DC preconditioning with rapamycin and aspirin, applied alone or in combination, on LPS-induced DC maturation and T-cell allostimulatory capacity. Preconditioning with aspirin but not rapamycin tended to reduce the number of mouse bone marrow-derived immature DCs expressing CD40 and major histocompatibility complex class II molecules upon LPS stimulation. Conversely, DC preconditioning with rapamycin, but not aspirin, reduced T-cell alloproliferative responses. A combination of rapamycin and aspirin was more effective than either drug applied alone with respect to inhibition of T-cell alloproliferation. The two agents in combination reduced numbers of CD4 + IFN-γ + Th1 and CD4 + IL-17 + Th17 effector cells while maintaining Foxp3 + regulatory T cells. These results suggest aspirin may moderately enhance rapamycin-mediated inhibition of DC allostimulatory capacity.